The Discourse and Platforms and the Consolidation of Values Problems and Solutions: خطاب المنابر وترسيخ القيم الإشكاليات والحلول - Aisyah Hasan (Sekolah Tinggi Ilmu Al-Quran Isy Karima Karanganyar, 2025)
The discourse of the pulpits has great importance in consolidating human values, especially after the diversity and multiplicity of its old means represented in mosques, and the new ones through modern technologies and social networks, especially in this era when human values ​​have become secondary. In current study it has been presented that the problems of discourse in the curriculum, language, and content, as well as in the means. Some solutions have been developed through which some of its problems can be overcome. Thus, it can be employed in the consolidation of human values ​​to the fullest. I have concluded that human values ​​are an ethical system, an integrated, necessary, improving one that works to create an optimal life for humanity in a world of chaos, the moral rift, and the lack of influential preachers. The preachers who are good or proficient in rhetoric, and by codifying the crystallization of our rhetorical approach, which requires us to review our strategic plans in preparing the sermon, because the weakness of the pulpits is the weakness of the call. It is empty on its thrones, so the preacher must pay attention to the phenomena, and the problems that the listeners are looking for solutions to monitor them, solve them legally, and explain their advantages and disadvantages.